An efficient cost based allocation approach for individual generators associated with the system. (August 2018) - Bhowmik, Debashish; Sinha, A.K.
Abstract: This paper presents a maiden alternative approach to the cost based allocation over the transmission network for individual generators associated with the system. A modified method is proposed by which the proportion of power going from an individual generator to the loads, and to the rest of the transmission network can be traced in a grid system. Also, the revenue collected from the customer side for all associated producers separately can be determined. The developed technique has been experimented successfully on a 39-bus New England Power System and to validate the method, the outcomes of the projected algorithm of the test system are compared with the power flow solution obtained by using the sequential quadratic programming method. The comparative analysis reveals that the results obtained from both the methods are nearly the same under different loading conditions, proving the accuracy and robustness of the proposed method.